2021
DOI: 10.1016/j.bj.2020.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features, laboratory findings and persistence of virus in 10 children with coronavirus disease 2019 (COVID-19)

Abstract: Background A pandemic caused by SARS-CoV-2 infection (COVID-19) has rapidly spread across the globe. Although many articles have established the clinical characteristics of adult COVID-19 patients so far, limited data are available for children. The aim of this study was to reveal the clinical features, laboratory findings and nucleic acid test results of ten pediatric cases. Material and methods In this retrospective single-center cohort study, pediatric cases with COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…These studies included a total of 104,058 laboratory-confirmed COVID-19 cases, of which 25,050 exhibited no symptoms at the time of testing and 7,220 remained asymptomatic. We identified 170 studies that reported asymptomatic infections ( 11 13 , 17 183 ), 332 studies that reported silent infections at the time of testing ( 10 12 , 14 , 17 20 , 23 27 , 31 , 32 , 35 40 , 42 44 , 46 , 47 , 49 , 50 , 52 , 53 , 56 58 , 60 66 , 68 , 69 , 73 75 , 77 79 , 81 , 84 , 87 , 90 94 , 97 , 99 , 101 , 103 , 104 , 106 , 111 , 113 116 , 118 , 119 , 121 123 , 125 , 127 , 128 , …”
Section: Resultsmentioning
confidence: 99%
“…These studies included a total of 104,058 laboratory-confirmed COVID-19 cases, of which 25,050 exhibited no symptoms at the time of testing and 7,220 remained asymptomatic. We identified 170 studies that reported asymptomatic infections ( 11 13 , 17 183 ), 332 studies that reported silent infections at the time of testing ( 10 12 , 14 , 17 20 , 23 27 , 31 , 32 , 35 40 , 42 44 , 46 , 47 , 49 , 50 , 52 , 53 , 56 58 , 60 66 , 68 , 69 , 73 75 , 77 79 , 81 , 84 , 87 , 90 94 , 97 , 99 , 101 , 103 , 104 , 106 , 111 , 113 116 , 118 , 119 , 121 123 , 125 , 127 , 128 , …”
Section: Resultsmentioning
confidence: 99%
“…This review included 81 articles published in English that in total included 3,557 pediatric patients. Of these, 2 were from the USA (46,86), was from Kore (58), 1 was worldwide ( 70 (46,47,75,81,82,90,104,108), 2 letters (77,79), 1 brief report (36), 2 case-control study (49,101), 2 cohort studies (66,70), 1 observational (84) and 5 observational cohort study (80,93,99,100,113) and the remained articles were descriptive studies. A total of 84 variables were extracted for this review.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Our observations corroborate those of previous studies. For example, Jian et al observed comparable elevated levels of LDH in pediatric patients, which they thought to be a possible sign of COVID-19 [ 17 ]. Similarly, Du et al observed that the value and positive rate of LDH were significantly greater in children than in adults in a study of 67 adult and pediatric COVID-19 patients [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lactate dehydrogenase (LDH) was recently identified as one of the most common biochemical parameters in COVID-19-infected children. It was deemed a prospective predictor of serum biochemical changes in the bodies of COVID-19-infected children [ 17 ]. LDH was found to be significantly high in two recent studies, where they compared the biochemical parameter with that of CT and chest radiographs in COVID-19 in children [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%